Kemampuan Berpikir Kreatif pada Model PJBL Pendekatan Open-Ended Ditinjau dari Gaya Belajar V-A-R-K - Restanto, Rudi; Junaedi, Iwan; Mulyono, Mulyono (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2023)
Creative thinking skills need to be developed in mathematics learning. The purpose of this study was to examine the quality of the Project Based Learning model with an Open-ended approach in improving mathematical creative thinking skills and to find patterns of creative thinking skills of grade XI vocational students in terms of learning styles. Creative thinking is a skill that must be possessed in the learning process because without the ability to think creatively a person will find it difficult to find solutions to problems, so it is possible that there will never be progress in his life. In the learning process, it is very important to pay attention to students' learning styles and appropriate learning models. This research uses a combination method. Learning style instrument was adapted from the VARK questionnaire.  From this study, it was found that Project Based Learning model with Open-ended approach is effective in improving mathematical creative thinking ability. There are differences in students' creative thinking abilities with various dominant learning styles. Students with combined learning styles show a more varied and high level of creative thinking skills.